Mobile phone-based surveillance system for slaughterhouses to report and monitor livestock diseases and syndromes in Uganda - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
The innovation was tested in Western Kenya (link #1) and is now being tested in Uganda across different livestock species, coupled with meat inspector trainings and consultations (link #2). High-level government and authoritative bodies are involved in the testing to improve sustainability and to improve evidence-based decisionmaking.